GLOBAL WELL-POSEDNESS OF THE PERIODIC CUBIC FOURTH ORDER NLS IN NEGATIVE SOBOLEV SPACES. (11th May 2018) - OH, TADAHIRO; WANG, YUZHAO
Abstract : We consider the Cauchy problem for the cubic fourth order nonlinear Schrödinger equation (4NLS) on the circle. In particular, we prove global well-posedness of the renormalized 4NLS in negative Sobolev spaces H^s(T), s>-13, with enhanced uniqueness. The proof consists of two separate arguments. (i) We first prove global existence in H^s(T), s>-920, via the short-time Fourier restriction norm method. By following the argument in Guo–Oh for the cubic NLS, this also leads to nonexistence of solutions for the (nonrenormalized) 4NLS in negative Sobolev spaces. (ii) We then prove enhanced uniqueness in H^s(T), s>-13, by establishing an energy estimate for the difference of two solutions with the same initial condition. For this purpose, we perform an infinite iteration of normal form reductions on the H^s -energy functional, allowing us to introduce an infinite sequence of correction terms to the H^s -energy functional in the spirit of the I -method. In fact, the main novelty of this paper is this reduction of the H^s -energy functionals (for a single solution and for the difference of two solutions with the same initial condition) to sums of infinite series of multilinear terms of increasing degrees.